Determining the noise impact on hearing using psychoacoustical noise dosimeter - CZYŻEWSKI, Andrzej; KOTUS, Józef; KOSTEK, Bożena (Archives of Acoustics, 2007)
This research study presents the designed noise dosimeter based on psychoacoustical properties of the human hearing system and, at the same time, evaluation of time and frequency characteristics of noise. The designed noise dosimeter enables assessing temporary threshold shift (TTS) in critical bands in real time. In this way it is possible monitoring the hearing threshold shift continuously for people who stay in the harmful noise conditions. Moreover, the psychoacoustical noise dosimeter (PND) provides the functionality which determines time causing an increase of the assumed hearing threshold shift along with time required for recovery of a hearing threshold toward its initial value. Noise exposure levels, its duration along with hearing examination have been first measured in the acoustically controlled environment. Pure-tone audiometry has been used for hearing examination. This has been conducted in constant time intervals, during noise exposure as well as during resting time (time required for hearing recovery). The examination aims at measuring hearing threshold at 4 kHz. The important part of this study is validation of the dosimeter performance in the real noise exposure situation. In this case the whole noise measurement scenario encompasses both noise exposure effects, and hearing examination before and after noise exposure. The hearing examination has been extended by the distortion products otoacoustic emission method (DPOAE). The measurement results obtained in real conditions have been compared with those which were computed by means of the presented psychoacoustical noise dosimeter.